2012
DOI: 10.1088/0031-9155/57/7/2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chamber response function influence on IMRT verification using 2D commercial detector arrays

Abstract: This work is devoted to studying the influence of chamber response functions on the standard IMRT verification for the different detector technologies available on commercial devices. We have tested three of the most used 2D detector arrays for radiotherapy dosimetry verification, based on air-ionization chambers and diode detectors. The response function has been carefully simulated using the Monte Carlo method and measured through slit and pinhole collimators. Although the response function of air-ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 19 publications
2
38
1
Order By: Relevance
“…12 The fill factor of the OD1500 array, which characterizes its sensitivity to misaligned MLC leaves, was determined as 0.86 with a single OD1500 measurement and 1.00 with two merged OD1500 measurements. For a single measurement with the OD729 array, a fill factor of 0.5 has been obtained, which meets the value published by Gago-Arias et al, 14 whereas fill factor 1.00 is achieved merging four measurements by which a geometry with adjacent chambers is simulated.…”
Section: Discussionsupporting
confidence: 83%
“…12 The fill factor of the OD1500 array, which characterizes its sensitivity to misaligned MLC leaves, was determined as 0.86 with a single OD1500 measurement and 1.00 with two merged OD1500 measurements. For a single measurement with the OD729 array, a fill factor of 0.5 has been obtained, which meets the value published by Gago-Arias et al, 14 whereas fill factor 1.00 is achieved merging four measurements by which a geometry with adjacent chambers is simulated.…”
Section: Discussionsupporting
confidence: 83%
“…At the depth beyond the dose maximum, the dose response function of the I'mRT MatriXX can be characterized by a Gaussian function. Similar results were obtained by Garcia-Vicente et al [27], Bednarz et al [12], Ulmer and Kaissl [29], Pappas et al [30], Yan et al [19], Fox et al [28], Gago-Arias et al [31] and Looe et al [32]. They concluded that the Gaussian convolution kernels are the best fit function to describe the detector response function beyond d max .…”
Section: Discussionsupporting
confidence: 75%
“…The single detector's dose response function of the I'mRT MatriXX array can be defined as the convolution kernel K(x) that transforms the true dose profile D(x) into the measured signal profile M(x) and thereby characterizes the broadening of the slit-beam dose profile [16,17,31,32]. It is affected by the detector size, the replacement of water by air, the wall and the central electrode of the detector as well as the geometrical form of the chamber itself [16,32].…”
Section: Dose Response Function Of a Single Detector Of The 2d Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used dose distribution measurement devices currently available are film 5 , 6 (radiochromic), arrays 7 , 8 (both ion chamber and diodes), and EPIDs. Film has a high resolution, but its use is very time‐consuming; it needs time before scanning, the scanning itself, and a calibration process.…”
Section: Introductionmentioning
confidence: 99%